ESTIMATION OF RETURNED BIOMASS AND NUTRIENTS IN OIL PALM PLANTATION IN ONE LIFE CYCLE - Irsa, Fuadi; Irsan, Fuadi; Anwar, Syaiful; Nugroho, Budi; Indriyati, Lilik Tri (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
Oil palm plantations development is still being a concern related to global trade and environment issues such as terrestrial carbon issue. The existing estimation of oil palm carbon absorption was only focused on standing biomass. Carbon which is derived from harvested biomass (FFB) and returned biomass through pruning has not much been studied in terms of oil palm carbon absorption. Besides C, returned biomass also contained essential nutrients such as N, P and K. The objectives of this research were to study the potency of biomass, carbon and nutrients (N, P and K) returned in one life cycle of oil palm. The result shows that the potency of returned biomass in one life cycle was 96.21 - 138.42 tons dry matter ha-1 or equivalent to 194.51 - 279.85 tons CO2 ha-1. While returned nutrient was 1.49 - 2.15 tons N ha-1 147.61 - 212.36 kg P ha-1 and 1.32 - 1.89 tons K ha